The Effects of Combinations of Cognitive Impairment and Pre-frailty on Adverse Outcomes from a Prospective Community-Based Cohort Study of Older Chinese People - Yu, Ruby; Morley, John E.; Kwok, Timothy; Leung, Jason; Cheung, Osbert; Woo, Jean (Frontiers in Medicine, 2018)
Abstract Objectives: To examine how various combinations of cognitive impairment (overall performance and specific domains) and pre-frailty predict risks of adverse outcomes; and to determine whether cognitive frailty may be defined as the combination of cognitive impairment and the presence of pre-frailty. Design: Community-based cohort study Participants: Chinese men and women (n=3,491) aged 65+ without dementia and/or Parkinson’s disease and/or frailty at baseline Measurements: Frailty was characterized using the Cardiovascular Health Study criteria. Overall cognitive impairment was defined by a Chinese Mini-Mental Status Examination (CMMSE) total score(<21/24/27, depending on participants’ educational levels); delayed recall impairment by a CMMSE delayed recall score(<3); language and praxis impairment by a CMMSE language and praxis score(<9). Adverse outcomes included poor quality of life, physical limitation, increased cumulative hospital stay, and mortality. Results: Compared to those who were robust and cognitively intact at baseline, those who were robust but cognitively impaired were more likely to develop pre-frailty/frailty after four years (P<0.01). Compared to participants who were robust and cognitively intact at baseline, those who were pre-frail and with overall cognitive impairment had lower grip strength (P<0.05), lower gait speed (P<0.01), lower limb strength (P<0.01), and poorer delayed recall at year 4 (OR,1.6;95%CI,1.2-2.3). They were also associated with increased risks of poor quality of life (OR,1.5;95%CI,1.1-2.2) and incident physical limitation at year 4 (OR,1.8;95%CI,1.3-2.5), increased cumulative hospital stay at year 7 (OR,1.5;95%CI,1.1-2.1), and mortality over an average of 12 years (OR,1.5;95%CI,1.0-2.1) after adjustment for covariates. There was no significant difference in risks of adverse outcomes between participants who were pre-frail, with/without cognitive impairment at baseline. Similar results were obtained with delayed recall and language and praxis impairments. Conclusion: Robust and cognitively impaired participants had higher risks of becoming pre-frail/frail over four years compared with those with normal cognition. Cognitive impairment characterized by an overall score or individual sub-domains improved the predictive power of pre-frailty for poor quality of life, incident physical limitation, increased cumulative hospital stay, and mortality. Our findings support to the concept that cognitive frailty may be defined as the occurrence of both cognitive impairment and pre-frailty, not necessarily progressing to dementia.